Pengembangan Kegiatan Ekstrakurikuler Bahasa Arab di Pondok Pesantren - Ni'mah Ziyadatul Khusnah; Kholisin Kholisin; Ahmad Munjin Nasih (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2020)
This study discusses the development of extracurricular activities in Arabic at Nurul Jadid Islamic Boarding School, Paiton-Probolinggo, which includes: 1) Types of activities, 2) Planning activities, 3) Implementation of activities, and 4) Evaluating activities. This study uses a qualitative descriptive method with a case study approach. The qualitative data in this study included extracurricular activities in Arabic. The data sources of this research are the core management and students in the LPBA. The instrument is the researcher himself (human instrument). Data collection was obtained through the results of distributing questionnaires, interviews, observation, and documentation. The results showed a number of things, namely (1) twelve extracurricular activities attended by students at ula and wushta levels with the hope that students often get used to listening to hiwar or Arabic conversations from native Arabs, and can apply them in daily conversations. day (2) Planning activities consist of student organizations, curriculum, schedule arrangements, activity themes, and regulations, (3) This activity is carried out every night after teaching and learning activities (KBM) and Friday from morning to evening, and (4) Evaluation of this activity is carried out once a month with the aim of finding solutions to problems experienced by students.